ANALISIS EFEK ANTESEDEN STRUKTUR MODAL PADA NILAI PERUSAHAAN - Ruli Indriani; Ratna Septiyanti; Ninuk Dewi Kusumaningrum; Usep Syaipudin (Faculty of Economics and Business, 2019)
The research aims to examine the antecedent variables of capital structure, such as profitability, firm size, investment opportunity set, managerial ownership, and dividend policy, and its effect on the firm value. We used 41 listed firms of the Indonesia Stock Exchange from manufacturing industry in 2012-2017 period. We used factor analysis to determine the representativeness of independent variables as the capital structure variables then we tested its effect on firm value by using multiple linear regression. The results indicate that profitability, firm size, investment opportunity set, managerial ownership, and dividend policy simultaneously have a statistically significance influence on capital structure. Partially, profitability has a statistically significance negative effect on capital structure, investment opportunity set has a statistically significance positive effect on capital structure, and managerial ownership has a statistically significancenegative effect on capital structure, while firm size and dividend policy have no statistically effect on capital structure. This research give an empirical evidence that capital structure have a statistically significance positive effect on firm value. This result have an implication that the antecedent effect of capital structure is positive and statistically significance on firm value.